Pembuatan Power Supply dengan Tegangan Keluaran Variabel Menggunakan Keypad Berbasis Arduino Uno - Nurlana, Muhammad Evanly (Electrical Engineering, Universitas Negeri Semarang, 2019)
Analog power supply generally still uses analog rounds (potentiometers) for its operation, so high accuracy is needed to get the direct output voltage in accordance with the needs of the user, and the price for the power supply with factory-made variable voltage has an expensive price. This research aims to make a microcontroller-based digital power supply using the keypad, and is designed to have a faster response to practical activities. The research method used is Methods Engineering. The steps in the engineering method include ideas, concepts, planning, design, development, and launch of a power supply prototype that has been made. The results showed that the accuracy of the output voltage of the prototype power supply according to the setting voltage showed good results, where the value of the error ratio between the multimeters with LCD display was an average error voltage of 0.02 volts without load, compared to the artificial power supply the factory that has an error comparison value between the multimeters and the LCD display there is a difference in the average error voltage of 0.76 volts without load. Voltage drop in the power supply prototype has a small value, where the voltage drop is measured at 0.09V with 12V voltage setting and 7 watt incandescent lamp load.